ON SAFE PLANT AND FODDER PRODUCTION ON 137CS CONTAMINATED SOILS - A. V. Panov; A. A. Muzalevskaya; R. M. Alexakhin; P. V. Prudnikov; E. V. Vlasenko (Радиационная гигиена)
The paper predicts the permissible levels of 137Cs contamination of agricultural lands where the obtaining of farm products in compliance with the existing standards is possible at different countermeasure scales in the affected areas. Exemplified by the south-western districts of the Bryansk region affected by the Chernobyl accident, the time periods are estimated when plant and fodder production in accordance with the radiological standards is ensured.